Radiative recombination in Cu2ZnSnSe4 thin films with Cu deficiency and Zn excess. (2nd November 2015) - Yakushev, M V; Márquez-Prieto, J; Forbes, I; Edwards, P R; Zhivulko, V D; Mudryi, A V; Krustok, J; Martin, R W
Abstract: Thin films of Cu2 ZnSnSe4 (CZTSe) with copper deficiency and zinc excess were fabricated at Northumbria University by the selenisation of metallic precursors deposited on Mo/glass and bare glass substrates. Absorption and photoluminescence (PL) measurements were used to examine the film on glass whereas films on Mo/glass were used to produce a solar cell with efficiency of 8.1%. Detailed temperature and excitation intensity analysis of PL spectra allows identification of the main recombination mechanisms as band-to-tail and band-to-band transitions. The latter transition was observed in the spectra from 6 to 300 K.